Primary myelofibrosis marrow-derived CD14(+)/CD34(-) monocytes induce myelofibrosis-like phenotype in immunodeficient mice and give rise to megakaryocytes - Manshouri, Taghi (PLoS One, 2019)
To confirm that neoplastic monocyte-derived collagen- and fibronectin-producing fibrocytes induce bone marrow (BM) fibrosis in primary myelofibrosis (PMF), we injected PMF BM-derived fibrocyte-precursor CD14(+)/CD34(-) monocytes into the tail vein of NOD-SCID-γ (NSG) mice. PMF BM-derived CD14(+)/CD34(-) monocytes engrafted and induced a PMF-like phenotype with splenomegaly, myeloid hyperplasia with clusters of atypical megakaryocytes, persistence of the JAK2(V617F) mutation, and BM and spleen fibrosis. As control we used normal human BM-derived CD14(+)/CD34(-) monocytes. These monocytes also engrafted and gave rise to normal megakaryocytes that, like PMF CD14(+)/CD34(-)-derived megakaryocytes, expressed HLA-ABC and human CD42b antigens. Using 2 clonogenic assays we confirmed that PMF and normal BM-derived CD14(+)/CD34(-) monocytes give rise to megakaryocyte colony-forming cells, suggesting that a subpopulation BM monocytes harbors megakaryocyte progenitor capacity. Taken together, our data suggest that PMF monocytes induce myelofibrosis-like phenotype in immunodeficient mice and that PMF and normal BM-derived CD14(+)/CD34(-) monocytes give rise to megakaryocyte progenitor cells.